Fracture rates lower in rural than urban communities: the Geelong Osteoporosis Study. Issue 6 (1st June 2002) - Sanders, K M; Nicholson, G C; Ugoni, A M; Seeman, E; Pasco, J A; Kotowicz, M A
Abstract : Background: Urban and rural communities differ in the incidence of several diseases including coronary heart disease and some cancers. Lower hip fracture rates among rural than urban populations have been reported but few studies have compared rural and urban fractures at sites other than the hip. Objective: To compare total and site specific fracture rates among adult residents of rural and urban communities within the same population. Design and setting: This is a population based study on osteoporosis in Australia. All fractures occurring in adult residents over a two year period were ascertained using radiological reports. The rural and urban areas are in close proximity, with the same medical, hospital, and radiological facilities permitting uniform fracture ascertainment. Main outcome measures: All fracture rates were age adjusted and sex adjusted to the Australian population according to the 1996 census of the Australian Bureau of Statistics and described as the rate per 10 000 person years. The p values refer to the adjusted rate difference. Results: The hip fracture rate (incidence per 10 000 person years) was 32% lower (39 v 57, p<0.001), and the total fracture rate 15% lower (160 v 188, p=0.004) among rural than urban residents, respectively. The lower fracture rates in the rural population were also apparent for pelvic fractures. Conclusion: In the older rural population, lower fracture rates at sites typically associated with osteoporosis suggest environmental factors may have a different impact on bone health in this community. If the national rate of hip fracture could be reduced to that of the rural population, the projected increase in hip fracture number attributable to aging of the population could be prevented.